Development of electroplating process for plating polyamides (Bangladesh Journal of Scientific and Industrial Research, 2013)
We report a method of converting non-conductive plastic surfaces into conductive by coating with copper based conductive paints onto polyamide6 (Nylon6) plastics to create a conducting surface for a subsequent copper deposition and thus for electroplating them. Nylon6 are basically hygroscopic materials and difficult to plate and hence conductive painting procedure has been adopted for electroplating them. The electroless plating procedure that is normally followed in plating of plastics has been avoided and thus a new method of plating on plastics has been presented in this research paper. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17333 Bangladesh J. Sci. Ind. Res. 48(3), 205-212, 2013